2015
DOI: 10.1002/bkcs.10552
|View full text |Cite
|
Sign up to set email alerts
|

Phase Segregation in the Mixed Alkyl Thiol Self‐assembled Monolayers on a Gold Surface at a High Incubation Temperature in a Sealed Container

Abstract: Self-assembled monolayers (SAMs) of mixed 1-octanethiol (OT) and 1-decanethiol (DT) that were formed on gold substrates at a high incubation temperature in a sealed container were characterized using scanning tunneling microscopy (STM) and X-ray photoelectron spectroscopy (XPS). In mixed-composition monolayer films, self-assembly of the mixture could induce phase separation into discrete molecular domains at higher incubation temperatures. Mixtures of the alkanethiol molecules affected the domain size, defect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…These observed particles could be correlated with the size of DNA aptamers, as similarly reported in previous studies. 32–34 After the HbA1c binding (Fig. 4c), particles with a height of about 4 nm were detected, which could be inferred to be the size of the HbA1c proteins.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…These observed particles could be correlated with the size of DNA aptamers, as similarly reported in previous studies. 32–34 After the HbA1c binding (Fig. 4c), particles with a height of about 4 nm were detected, which could be inferred to be the size of the HbA1c proteins.…”
Section: Resultsmentioning
confidence: 92%
“…A previous study suggested that the mixture of these compounds should be homogenized under sonication before use. 32,33 Fig. S2c † clearly shows that the ultrasonic pretreatment of the alkanethiol mixture for 1 min before SAM formation signicantly improved the surface distribution of MHDA molecules with the persistence of a few particles.…”
Section: Characterization Of Surface Modicationmentioning
confidence: 97%